Rare earth doped fiber lasers and amplifiers - Digonnet, Michel J. F. (Optical engineering (Marcel Dekker, Inc.), 1993)
Examines the current technology of rare earth doped fibres, the laser sources and amplifiers made with these fibres, and fibre communication systems incorporating erbium-doped fibre amplifiers. The text contains over 875 equations, figures and tables.